Coated paper
Patent Information
- Application Number
- CN202410572487.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2021-10-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-10-14
Smart Images

Figure SMS_5 
Figure SMS_6 
Figure SMS_14
Abstract
Description
[0001] This application is a divisional application of patent application number 20218000653.0.
[0002] This invention relates to a coated paper, a method for manufacturing the coated paper, the use of the coated paper as a packaging material, and packaging containing the coated paper.
[0003] The term "packaging" generally refers to covering or (partially or completely) wrapping an object, especially for its protection or better handling. Therefore, packaging materials include the materials that form such packaging.
[0004] For example, packaging materials can be based on paper, plastic, and / or metal. This invention relates to paper-based packaging materials.
[0005] The primary requirement for packaging materials of any origin is to protect the packaged product from external influences and prevent leakage. To this end, depending on the product being packaged and the packaging process, packaging materials should meet different standards. In addition to so-called barrier properties against water, grease, oxygen, or mineral oils, suitable packaging materials should also meet mechanical and process-specific requirements. Depending on the packaging system, packaging materials should have sufficient tear resistance, a suitable coefficient of friction, and flexibility; they should be heat-sealable or compatible with cold-seal adhesives; they should be printable from the outside; and they should not lose their protective function throughout the transshipment and packaging process.
[0006] Based on its composition and areal density, paper can meet many mechanical requirements, but due to its physical properties and porous structure, it requires additional coatings to provide it with properties such as heat-sealing or barrier properties.
[0007] Known paper-based coated packaging materials typically contain compounds such as polyvinylidene chloride (containing halogens), or composites of paper and metal or plastic foil, which require improved tear strength. This can lead to operational problems with packaging equipment and / or make them generally non-recyclable due to excessive coating content, adhesive components, or the formation of so-called sticky substances via the flow of paper fibers.
[0008] Polyvinyl alcohol (PVA) is a well-known linear, water-soluble, biodegradable barrier coating, including for use in paper. Here, such coatings exhibit good barrier properties against oils, greases, oxygen, solvents, and other nonpolar gases, liquids, or solids. However, due to its hydrophilicity, PVA exhibits very high permeability to polar compounds such as water. This also affects its barrier effect against nonpolar migrating substances, as PVA readily absorbs moisture, swells, and thus forms pathways through the barrier coating at the molecular level.
[0009] Numerous attempts have been made to achieve barrier degradation at relative humidity above 50 or 60%, for example, through the addition of pigments (e.g., disclosed in WO 2010 / 129032) or through crosslinking of polymer chains (e.g., disclosed in WO 2020 / 109401 or US 6,444,750). However, these microscopic defects not only hinder the use of polyvinyl alcohol as a barrier, but more importantly, macroscopic defects arising from mechanical stress in packaging and conversion systems impair the applicability of polyvinyl alcohol.
[0010] Polyvinyl alcohol is understood to refer to fully saponified polyvinyl acetate, which is a (thermoplastic) plastic material of formula (I) and is usually synthesized by free radical polymerization of vinyl acetate.
[0011] (I)
[0012] The ester groups in polyvinyl acetate can be relatively easily saponified with alkali, thereby converting the polymer into polyvinyl alcohol, making it hydrophilic and water-sensitive.
[0013] Partially saponified polyvinyl acetate is also known as partially saponified polyvinyl alcohol.
[0014] In this invention, the term "partially saponified polyvinyl acetate" may be used synonymously with the term "partially saponified polyvinyl alcohol".
[0015] In this context, the degree of saponification indicates the proportion of ester groups that have been saponified and are now present as -OH groups. For example, polyvinyl alcohol with a saponification degree of 90% is a vinyl acetate polymer, in which 90% of the initially present ester groups have been saponified. Therefore, this polyvinyl alcohol contains 90% OH groups and 10% ester groups. At a saponification degree of 100%, only OH groups are present because all the initially present ester groups have been saponified.
[0016] Besides pure homopolymers, many polyvinyl alcohol copolymers also have significant technical implications. A copolymer is understood to refer to all polymers composed primarily of vinyl alcohol or vinyl acetate units (>50%), regardless of the amount of different monomers used in the synthesis.
[0017] This polyvinyl alcohol copolymer preferably contains polyvinyl alcohol.
[0018] In a narrow sense, saponification here refers to the hydrolysis of esters by hydroxides such as aqueous sodium hydroxide solution or by a specific enzyme (esterase). Unlike ester hydrolysis (the reverse reaction of esterification), these are irreversible because the carboxylic acid lacks the proton necessary for esterification. The products of the reaction are the salts of the alcohol and acid that make up the ester (carboxylation). In a broader sense, any hydrolysis of an ester can be called saponification.
[0019] The object of this invention is to overcome the shortcomings of known materials and provide a material suitable as a packaging material, particularly for oxidatively sensitive and oily foods, and which can be used to produce packaging, such as tubular bags, by means of heat-sealing or cold-sealing processes. Furthermore, this material should not contain any barrier layer based on halogen-containing compounds. In addition, the material according to the invention should have one or more of the following properties compared to known packaging materials:
[0020] Improved oxygen barrier properties, improved grease barrier properties, improved mineral oil barrier properties, improved wrinkle resistance / flexibility, recyclability via waste paper recycling, and improved heat-sealing performance.
[0021] Improved cold-sealing performance (compatible with sealing media, such as water-based cold sealants), high tear resistance, no alteration of the packaged product's odor, aroma-sealing, and printable exterior. The material should also have improved water vapor barrier properties, and the sealed seams should be as moisture-proof as possible. The packaging material should also be suitable for metallization, particularly in the micron and nanometer ranges, to further optimize barrier properties when needed. Finally, the material should be produced as economically as possible.
[0022] This objective is achieved by a coated paper according to the invention, namely, a coated paper comprising a base paper and a barrier layer applied thereon, the barrier layer comprising at least one polymer, and characterized in that the polymer comprises at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer, each having an onset temperature determined by DSC of less than 210°C.
[0023] The initial temperature is determined by DSC as follows:
[0024] The extrapolated onset temperature (according to DIN EN ISO 11357-1:2010-03) is the intersection of the extrapolated baseline and the inflection tangent at the start of the melting or crystallization peak in the DSC measurement. The baseline and inflection tangent are determined by the temperature-dependent heat flux signal. For purely homogeneous materials, the onset temperature can be specified as the melting temperature. Compared to the peak temperature, the onset temperature is less dependent on the heating rate and sample mass. Furthermore, the onset temperature is often used for temperature calibration of the DSC.
[0025] Paper coated in this way is particularly suitable as packaging material for oxidation-sensitive and oily substances, especially food, and can be used to produce bags by means of heat sealing or cold sealing, with the cold sealing process using water-based cold-sealing adhesives. Furthermore, there is no need for a barrier layer based on halogen-containing compounds.
[0026] Compared to fully saponified polyvinyl alcohol (PVOH) or polyethylene glycol (EVOH), partially saponified polyvinyl alcohol has the advantage of a much lower optimal sealing temperature in heat-sealing processes. The strength of the sealed joint is not negatively affected. Furthermore, partially saponified polyvinyl alcohol has a slightly lower viscosity at the same concentration. High viscosity is quite disadvantageous because the PVOH solution must be diluted more significantly in this case, thus requiring a larger amount of water to dry during coating. This not only incurs energy costs and thus necessitates coating equipment with higher drying capacity, but is also technically difficult to achieve, depending on the desired coating weight. Moreover, the diffusion and drying process of water molecules are inherently slower at high viscosity. Additionally, the accumulation of gaseous water in the coating may more easily lead to the formation of macroscopic coating defects.
[0027] Therefore, partially saponified polyvinyl alcohol or partially saponified polyvinyl alcohol copolymers, such as polyvinyl alcohol, are superior to fully saponified variants.
[0028] The coated paper according to the present invention is further characterized by improved oxygen barrier properties, improved oil barrier properties, improved mineral oil barrier properties and improved water vapor barrier properties.
[0029] The coated paper according to the invention also has improved wrinkle resistance without compromising the barrier effect, and is further characterized by high tear strength.
[0030] The coated paper according to the present invention can also be recycled from waste paper.
[0031] If the coated paper according to the invention is used as a packaging material for food, its main feature is that it does not affect and / or change the taste of the packaged food.
[0032] The coated paper according to the invention also has heat-sealing properties and exhibits improved cold-sealing performance (compatible with sealing media, such as water-based cold-sealing adhesives), and each sealed joint has sufficient moisture resistance.
[0033] The coated paper according to the invention is also easy to print on the uncoated side (outer side).
[0034] The coated paper according to the invention is also suitable for metallization in the micron and nanometer ranges to further optimize barrier properties when needed.
[0035] Finally, the coated paper according to the invention can be produced relatively easily and has a low coating weight and can be recycled via waste paper recycling.
[0036] In the following text, the terms “including, containing and comprising” may also mean “consisting of”.
[0037] The term "hydrophobic" refers to a substance that cannot be mixed with water or can only be wetted by water using a surfactant. The term "hydrophilic" refers to a substance that can be mixed with water or can be wetted by water without the use of a surfactant. Hydrophobic polymers are also called nonpolar polymers, and hydrophilic polymers are also called polar polymers.
[0038] Hydrophobicity or hydrophilicity can be defined, for example, by the logP value. Octanol / water partition coefficient K. ow (For example, the sign for the octanol / water partition coefficient is also common and correct.) It is a dimensionless partition coefficient known to those skilled in the art, representing the ratio of the concentrations of a chemical substance in a two-phase system formed by n-octanol and water, and is therefore a measure of the hydrophobicity or hydrophilicity of the substance. The logP value is the n-octanol-water partition coefficient K. ow The decimal logarithm. The following is correct:
[0039] = P = And log P = log = log c o Si - c w Si
[0040] Where c o Si = The concentration of chemicals in the octanol phase, and
[0041] c w Si = The concentration of chemical substances in the water-rich phase.
[0042] If a substance is more soluble in fatty solvents (such as n-octanol), then K ow If K is greater than 1, then it is more soluble in water. ow The value is less than 1. Therefore, logP is positive for hydrophobic / oleophilic substances and negative for hydrophilic / oleophobic substances.
[0043] Polyvinyl alcohol has low permeability to oxygen, mineral oil, fats and other nonpolar migrating substances due to its relatively high hydrophilicity.
[0044] In addition, ethylene-containing polymers, such as (saponified) polyvinyl alcohol, have lower water vapor permeability, which can be attributed to the ethylene content and the corresponding lower hydrophilicity.
[0045] There are no restrictions in principle on the base paper used in the coated paper according to the present invention.
[0046] However, the preferred surface density of the base paper is 20 to 120 g / m². 2Preferably 40 to 100 g / m 2 .
[0047] More preferably, the paper has a composition of 10 to 80% long fiber content, preferably 20 to 50%, and 20 to 90% by weight, preferably 50 to 80% by weight short fiber content.
[0048] Long fibers are understood to be fibers with a length of 2.6 to 4.4 mm, while short fibers are understood to be fibers with a length of 0.7 to 2.2 mm.
[0049] In addition, it may contain 0% to 20%, preferably 0% to 5% of fillers (preferably excluding the value of 0%), such as GCC (heavy calcium carbonate, known for example under the trade names Hydrocarb 60 or Hydroplex 60), PCC (precipitated calcium carbonate, known for example under the trade name Precarb 105), natural kaolin and / or talc, as well as commonly used additives, such as retention aids and / or sizing agents.
[0050] The advantages of this base paper lie in its high flexibility and its good processability in existing packaging machines for flexible materials (such as plastic foil), maintaining high machine availability, and achieving the necessary puncture resistance.
[0051] Common packaging machines include, for example, vertical and horizontal filling and sealing machines used to produce stand-up pouches, flow packaging, pillow packaging, etc. These machines combine two webs of the same or different materials together and join them by heat sealing, such as pallet sealing machines, box conveyor belts (also vacuum), bagging and sealing machines, thermoforming packaging machines, linear filling machines that seal packages by applying a cap through heat sealing, packaging machines with a final heat sealing step, blister packaging machines, and X-fold packaging machines.
[0052] More preferably, the coated paper according to the invention is characterized in that there is a pre-coating containing at least one inorganic pigment and a polymer binder between the base paper and the barrier layer.
[0053] Inorganic pigments are preferably in the form of flakes and particularly contain talc, precipitated calcium carbonate or silicates, preferably layered silicates and very particularly preferably kaolin.
[0054] Suitable polymeric binders include, in particular, acrylate-based or styrene / butadiene-based binders. In principle, all polymers that can be used as pigment and coating binders in the paper industry are suitable. Starch-based binders (modified starch solutions, cross-linked starch dispersions, so-called bio-latex) and polymer-starch hybrid latexes are also possible.
[0055] The polymer adhesive preferably comprises a polyacrylate-based polymer adhesive.
[0056] The pre-coating can generally be a hydrophobic pre-coating.
[0057] In another implementation, the pre-coating is generally hydrophilic.
[0058] The pre-coating preferably contains 1 to 70% by weight, more preferably 5 to 50% by weight, of a polymeric binder. This amount is relative to the dried pre-coating in the final product.
[0059] The pre-coating further preferably contains 50 to 95% by weight, more preferably 80 to 90% by weight, of inorganic pigments. This amount is relative to the dried pre-coating in the final product.
[0060] In addition, the pre-coating may contain additives, such as thickeners, e.g., acrylate-based thickeners, surfactants, and / or rheology modifiers. Crosslinking agents may also be considered. Preferably, the pre-coating comprises a zirconium-based crosslinking agent and is itself crosslinked with formaldehyde.
[0061] These additives are preferably present in an amount of 0 to 2% by weight, more preferably greater than 0 to 2% by weight, and preferably excluding 0%. This amount is relative to the dried pre-coating in the final product.
[0062] The preferred application rate of the pre-coating is 1 to 10 g / m 2 Especially preferred is 2 to 6 g / m 2 This amount is relative to the dried pre-coating in the final product.
[0063] Applying such a pre-coating (also known as a primer) has the advantage of sealing the paper surface, for example, and causing other barrier layers applied thereon to migrate only slightly into the paper, thus generating sufficient interlayer adhesion. Furthermore, the pre-coating reduces the average roughness depth of the base paper and provides advantageous "retention," characterized by its application covering the entire surface and defining the surface energy, thus allowing for optimal formation of the applied barrier layer. Additionally, the pre-coating conducts interlayer adhesion between the base paper and the barrier layer, which can be important for subsequent sealing applications.
[0064] The barrier layer applied to the pre-coating comprises at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer. The formulation used in the processing preferably comprises 10 to 100% by weight, particularly preferably 50 to 99.8% by weight of the polymer.
[0065] The barrier layer may further include additives such as thickeners (e.g., acrylate-based thickeners), surfactants (e.g., sulfosuccinates / salts), stretching rheology modifiers (e.g., polyacrylamide, carboxymethyl cellulose, polyvinyl alcohol), and / or crosslinking agents (e.g., aldehydes and polyaldehydes, zirconates / salts, polyvalent epoxides, epichlorohydrin resins, and / or hydrazides).
[0066] These additives are preferably contained in an amount of 0.1 to 1% by weight, relative to the total weight of the barrier layer.
[0067] In one embodiment, and more preferably, the coated paper according to the invention is characterized in that at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer has an average molecular weight of less than 100,000 g / mol.
[0068] In another embodiment, and more preferably, the coated paper according to the invention is characterized in that at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer has an average molecular weight greater than 30,000 g / mol or greater than 40,000 g / mol or greater than 50,000 g / mol or greater than 60,000 g / mol or greater than 70,000 g / mol.
[0069] In one embodiment, more preferably, the coated paper according to the invention is characterized in that at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer has a saponification degree of 30% to 100%.
[0070] In another embodiment, and more preferably, the coated paper according to the invention is characterized in that at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer has a saponification degree of 30% to less than 100%.
[0071] In another embodiment, and more preferably, the coated paper according to the invention is characterized in that at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer has a saponification degree of less than 95% or 30% to 95%.
[0072] In another embodiment, and more preferably, the coated paper according to the invention is characterized in that at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer has a saponification degree of 95% to 100%.
[0073] In another embodiment, and more preferably, the coated paper according to the invention is characterized in that at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer has a saponification degree of 95% to less than 100%.
[0074] In another embodiment, and more preferably, the coated paper according to the invention is characterized in that at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymer has an onset temperature of less than 200°C as determined by DSC.
[0075] Further preferably, the coated paper according to the invention is characterized in that the at least one polymer comprises partially saponified polyvinyl alcohol with a saponification degree of less than 95% or 30% to 95%, an average molecular weight greater than 0 and less than 100,000 g / mol, and an onset temperature of less than 200°C as determined by DSC.
[0076] In another embodiment, and more preferably, the coated paper according to the invention is characterized in that the at least one polymer comprises partially saponified polyvinyl alcohol having a saponification degree of 95% to 100%, an average molecular weight greater than 70,000 g / mol, and an onset temperature less than 200°C as determined by DSC.
[0077] In another embodiment, and more preferably, the coated paper according to the invention is characterized in that the at least one polymer comprises a partially saponified polyvinyl alcohol copolymer, preferably a partially saponified polyvinyl alcohol, having a saponification degree of 95% to 100%, an average molecular weight greater than 60,000 g / mol, and an onset temperature less than 210°C as determined by DSC.
[0078] It has been shown that partially saponified polyvinyl alcohol copolymers, such as polyvinyl alcohol, are generally softer than polyvinyl alcohol.
[0079] In another embodiment, preferably, the coated paper according to the invention is characterized in that the at least one polymer is a partially saponified polyvinyl alcohol with a saponification degree of 1% to 95%, an average molecular weight greater than 0 and less than 100,000 g / mol, and an onset temperature of less than 200°C as determined by DSC; a partially saponified polyvinyl alcohol with a saponification degree of 95% to 100%, an average molecular weight greater than 70,000 g / mol, and an onset temperature of less than 200°C as determined by DSC; and / or a partially saponified polyvinyl alcohol copolymer with a saponification degree of 95% to 100%, an average molecular weight greater than 60,000 g / mol, and an onset temperature of less than 210°C as determined by DSC, preferably a mixture of partially saponified polyvinyl alcohol.
[0080] The degree of saponification is determined according to DIN EN ISO 3681 as follows:
[0081] PVOH (1 g) was mixed with deionized water (70 mL) and neutralized ethanol (30 mL) and heated under reflux until completely dissolved. After cooling, the solution was neutralized with caustic soda solution (0.1 M). In the case of partially saponified PVOH, a further amount of caustic soda solution (50 mL, 0.1 M) was added and the mixture was heated under reflux (60 min). In the case of fully saponified PVOH, a reduced amount of further caustic soda solution (25 mL, 0.1 M) was used to prevent the absorption of excess carbon dioxide from the potassium alkali, and the reflux time was also reduced (30 min). Subsequently, the excess potassium alkali was back-titrated with hydrochloric acid (0.1 M) using phenolphthalein as an indicator. A blank test was performed in parallel.
[0082] The degree of saponification (%) can be calculated according to Equation 1:
[0083]
[0084] The number of esters is determined according to Equation 2:
[0085]
[0086] The average molecular weight was determined by size exclusion chromatography (GPC) under the following conditions:
[0087] Eluent: DMSO + 0.1 M LiCl; Pre-column: 10 µm, guard plate, ID 8.00 mm x 50.00 mm; Column: 10 µm, 30 Å, ID 8.00 mm x 300.00 mm; 10 µm, 3000 Å, ID 8.00 mm x 300.00 mm; 10 µm, 3000 Å, ID 8.00 mm x 300.00 mm; Pump: 1260 HPLC-pump; Flow rate: 1.0 mL / min; Injector: 1260 autosampler; Injection volume: 200 µL; Sample concentration: 5.0 g / L; Temperature: 80℃; Detector: SECcurity 2 Refractive index detector (RI) - WEG eta 1001 HT viscometer; Calculations: WinGPC UniChrom version 8.33
[0088] The sample was dissolved in a solvent (5 mg / mL) at 80°C for 3 hours and then injected via an Autosampler.
[0089] To determine the calibration curves, several PMMA standards with different molecular weights were measured. The calibration curves were then converted to a universal calibration curve by measuring the intrinsic viscosity.
[0090] More preferably, the coated paper according to the invention is characterized in that, at a dry content of 4%, the polyvinyl alcohol has a strength of less than 30 mPa. s or less than 20 mPa s, especially less than 15 mPa The viscosity of s.
[0091] Viscosity was measured at 23°C using a Brookfield viscometer at 100 rpm.
[0092] Viscosities within this range offer several advantages: higher solids content can be used in applications, thus requiring less energy for drying; additionally, higher processing speeds can be achieved. Besides economic advantages, this also allows for the use of larger drying windows in coating equipment.
[0093] The coated paper according to the invention preferably has a breaking strength of >80 N / 15 mm, preferably >90 N / 15 mm, in the running direction and a breaking strength of >40 N / 15 mm, preferably >50 N / 15 mm, transverse to the running direction of the paper.
[0094] The coated paper according to the invention further preferably has a dynamic coefficient of friction of <0.7, more preferably <0.6, and particularly preferably <0.5. This refers to the friction between coated surfaces (coating to coating).
[0095] More preferably, the coated paper according to the invention is characterized in that the areal density of the applied barrier layer is 5 to 20 g / m² relative to the dried final product (air-dried). 2 Preferably 8 to 12 g / m 2 .
[0096] Further preferably, the coated paper according to the invention is characterized in that the barrier layer can be wetted by a common water-based cold-sealing adhesive. For this purpose, the surface energy of the barrier coating is > 40 mN / m, preferably > 50 mN / m, and particularly preferably > 55 mN / m.
[0097] This wettability of the barrier layer has the following advantages: no uncoated areas are formed during the application and drying of the cold-sealing adhesive, and it also provides sufficient adhesion for application.
[0098] More preferably, the coated paper according to the present invention is characterized in that the oxygen permeability (cm) of the coated paper is... 3 / m 2 / d (23℃, 0% relative humidity) less than 10, preferably less than 5.
[0099] More preferably, the coated paper according to the present invention is characterized in that the oxygen permeability (cm) of the coated paper is... 3 / m 2 / d (23℃, 50% relative humidity) less than 10, preferably less than 5.
[0100] More preferably, the coated paper according to the present invention is characterized in that the oxygen permeability of the coated paper is g / m 2 / d (23℃, 70% relative humidity) less than 20, preferably less than 10.
[0101] More preferably, the coated paper according to the present invention is characterized in that the oxygen permeability of the coated paper is g / m 2 / d (23℃, 80% relative humidity) less than 25, preferably less than 15.
[0102] Oxygen permeability (or oxygen transmission rate - OTR) is determined according to ISO 15105-2.
[0103] More preferably, the coated paper according to the invention is characterized in that it has grease barrier properties corresponding to test condition I according to DIN 53116.
[0104] The coated paper according to the invention preferably does not lose this grease barrier property due to the mechanical stress of the 180° crease (applied by a roller, which applies a load of 330 g / cm on the resulting crease), wherein the coating can be on the inside (inner crease) or the outside (outer crease).
[0105] More preferably, the coated paper according to the present invention is characterized in that the coated paper has a density of <10 g / m³. 2 / d mineral oil barrier properties (hexane).
[0106] Mineral oil barrier properties were determined by pouring hexane into a beaker (solvent-resistant), sealing it with coated paper, and monitoring the weight reduction over time.
[0107] More preferably, the coated paper according to the invention is characterized in that it has water vapor barrier properties. This remains unchanged even when the coating comes into contact with grease, but not all water vapor barrier properties are like this.
[0108] More preferably, the coated paper according to the invention is characterized in that it has anti-crease properties in the uncreased state, in the inner crease and the outer crease.
[0109] The coated paper according to the invention is characterized by its recyclability via waste paper recycling.
[0110] The coated paper according to the invention is heat-sealable, and preferably has a seam strength of >3.5 N / 15 mm, particularly >5.0 N / 15 mm, at the optimal sealing temperature. The seam strength of the coated paper is determined as follows:
[0111] The coated paper is sealed for 0.3 seconds at 3.3 bar in the transverse direction of paper travel at a temperature of 100°C to 230°C, and the strength of the seal joint is determined according to DIN 55529 (2012).
[0112] The term "heat-sealing" is preferably understood to mean bonding two layers of coated paper together by localized heat input and / or pressure. In a further embodiment, the coated side of the paper can also be heat-sealed to the opposite side of the paper itself or to another paper.
[0113] Furthermore, the coated paper according to the invention is also cold-sealable due to its compatibility with common cold-sealing media. Cold sealing is generally understood to refer to the application of a cold-sealing adhesive to the portion of a flat packaging material to be sealed by a pressure process. Cold-sealing adhesives have the characteristic that they only produce an adhesive effect when and after the pressure between the sealing clamps of the packaging machine increases; otherwise, they have no tack or only limited tack.
[0114] Heat-sealing paper and cold-sealing paper are characterized by their high moisture resistance in sealing joints.
[0115] The coated paper according to the present invention is also tear-resistant.
[0116] The coated paper according to the present invention is also characterized in that it does not affect the taste of the food packaged therein.
[0117] The coated paper according to the present invention can also be metallized in the nanoscale, for example with Al2O3 or Al.
[0118] More preferably, the coated paper according to the invention is characterized in that other layers comprising metals, especially aluminum, and / or metal oxides, especially aluminum oxide and / or silicon oxide, are applied to the barrier layer.
[0119] The coated paper according to the present invention can be economically obtained using known production methods.
[0120] However, it is preferred to obtain the coated paper according to the invention by means of applying an aqueous suspension containing a barrier layer starting material onto the base paper, wherein the applied aqueous suspension has a solid content of 5 to 50% by weight, preferably 10 to 30% by weight, and is applied by a curtain coating method, preferably a double curtain coating method, at an operating speed of a coating equipment of at least 200 m / min.
[0121] This method is particularly advantageous from an economic point of view, and also because of its uniform application across the paper web.
[0122] If the solids content is below approximately 10% by weight, economic efficiency decreases because a large amount of water must be removed through gentle drying in a short time, which negatively impacts coating speed. On the other hand, if the solids content exceeds 50% by weight, this only leads to increased technical input to ensure the stability of the coating curtain material and the drying of the coating film during the coating process, as the machine must again operate at high speed in this case.
[0123] In curtain coating, a curtain of free-falling coating dispersions is formed. The coating dispersion in the form of a thin film (curtain) is "poured" onto the substrate by free fall, thereby applying the coating dispersion onto the substrate. Document DE 10 196 052T1 discloses the use of curtain coating in the production of information recording materials, wherein multilayer recording layers are achieved by applying a curtain composed of multiple coating dispersion films onto a substrate.
[0124] In a preferred embodiment of the method according to the invention, the aqueous degassing coating suspension has a pressure of about 100 to about 800 mPa. The viscosity of s (Brookfield, 100 rpm, 20°C). If the viscosity is below approximately 100 mPa... The value of s may exceed approximately 800 mPa. The value of s results in the coating composition being difficult to pass through the coating unit. Particularly preferably, the viscosity of the aqueous deaerated coating suspension is about 200 to about 500 mPa. s.
[0125] In a preferred embodiment, the surface tension of the aqueous coating suspension can be adjusted to approximately 25 to approximately 70 mN / m, preferably to approximately 35 to approximately 60 mN / m (measured according to the standard of bubble pressure tension determination (ASTM D 3825-90), as described below), to optimize the process. The coating process can be better controlled by determining the dynamic surface tension of the coating material and by selectively adjusting it in a targeted manner by choosing a suitable surfactant and determining the required amount of surfactant.
[0126] It has been shown that polyvinyl alcohol solutions require significantly less surfactant to produce the same surface tension compared to dispersions, especially those with small particle sizes and therefore high particle surface areas.
[0127] Dynamic surface tension is measured using a bubble pressure tensiometer. It measures the maximum internal pressure of a bubble formed in a liquid via a capillary. According to the Young-Laplace equation, the internal pressure p (Laplace pressure) of a spherical bubble depends on the radius of curvature r and the surface tension σ:
[0128]
[0129] If bubbles are generated at the tip of a capillary in a liquid, the curvature first increases and then decreases, resulting in a maximum pressure. The curvature is at its maximum when the radius of curvature equals the capillary radius, and therefore the pressure is at its maximum.
[0130] The pressure curve during bubble pressure measurement, and the location of the maximum pressure:
[0131] The radius of the capillary is determined by a reference measurement using a liquid (usually water) with a known surface tension. If the radius is known, the surface tension can be calculated from the maximum pressure, pmax. Since the capillary is immersed in the liquid, the hydrostatic pressure p0, resulting from the immersion depth and liquid density, must be subtracted from the measured pressure (this is done automatically in modern measuring instruments). This yields the following formula for the bubble pressure method:
[0132]
[0133] The measured values correspond to the surface tension at a certain surface age, which is the time from the start of bubble formation to the occurrence of the maximum pressure. By changing the rate of bubble formation, the dependence of surface tension on surface age can be recorded, thus plotting a curve of surface tension changing over time.
[0134] This dependence plays a crucial role in the use of surfactants because, in many processes, the interfacial tension equilibrium cannot be reached simply because the diffusion and adsorption rates of surfactants are sometimes low.
[0135] Individual coatings can be formed online on a paper machine with a coating unit, or offline on a coating machine during a single coating process.
[0136] In a further implementation, the following methods can also be used to apply the individual layers to the base paper:
[0137] The barrier layer can be applied to the base paper and / or a pre-existing pre-coating by means of printing methods.
[0138] The barrier layer can be applied to the base paper and / or a pre-existing pre-coating by extrusion.
[0139] The advantage of this technology is that it can apply significantly more material, but this is only meaningful if the entire product does not need to be recyclable like paper. On the other hand, the disadvantages are lower application speed, higher energy consumption, and higher minimum application weight.
[0140] The barrier layer can be applied by laminating paper, for example, by applying it to the base paper and / or a pre-existing pre-coated layer in the form of a plastic material film.
[0141] Barrier layers and pre-coatings can also be applied sequentially in multiple application steps.
[0142] The present invention also relates to coated paper that can be obtained by the above method.
[0143] Due to its relatively high polarity, barrier layers are also suitable for applying additional barriers in the form of polymer aqueous solutions or dispersions via melt extrusion or with film lamination.
[0144] If desired, all barrier properties of the barrier layer can be improved by applying an ultrathin metal layer, metal oxide layer, or other inorganic compound through vapor deposition, or especially vacuum vapor deposition. Such thin barrier layers are only effective when they adhere to a very smooth, flexible substrate free of particles (e.g., inorganic pigments) and can form a sealing layer thereon. The higher surface energy of the barrier layer, especially the composite polymer, is beneficial for the layer adhesion of polar materials such as metal oxides and other inorganic oxides, as well as polarizable conductive materials such as metals. Paper obtained in this way can then be made sealable by applying a heat-sealing layer or a cold-sealing adhesive.
[0145] The present invention also relates to the use of coated paper as described above, or coated paper obtainable by the methods described above, as packaging material.
[0146] Finally, the present invention also relates to the use of coated paper as described above, or coated paper obtainable by the methods described above, as a food packaging material, particularly for packaging materials of oily and oxidation-sensitive foods.
[0147] The present invention further preferably relates to the use of coated paper as described above, or coated paper obtainable by the methods described above, as packaging material for, for example, cereal bars, chocolate, chocolate-containing products, or potato chips.
[0148] In a further preferred embodiment of the invention, the coated paper according to the invention is applied to cardboard or paperboard, particularly by lamination or bonding.
[0149] Finally, the invention also relates to the use of composite materials in which the coated paper according to the invention is applied to cardboard or paperboard (especially by lamination or bonding) as packaging materials for food, especially oily and oxidation-sensitive foods.
[0150] In this way, packaging materials that combine the advantages of both material components and the aforementioned advantages of coated paper can be produced simply and economically, such as increased strength and stiffness of cardboard or paperboard compared to coated paper. For example, starch or aqueous dispersion adhesives can be used for application.
[0151] Preferably, the coated paper can therefore be a component of packaging materials based on cardboard or paperboard.
[0152] Using these packaging materials according to the invention, heavier foods can be packaged securely and presented attractively to consumers in upright packaging in retail stores.
[0153] These packaging materials are preferably paper, cardboard, or paperboard of a uniform material type having a mass fraction of more than 95% by weight. Another advantage of the invention is that these packaging materials according to the invention are not composite packaging according to German Packaging Act §3(5), and therefore this embodiment of the invention significantly contributes to reducing the environmental impact of packaging waste.
[0154] The present invention also relates to packaging comprising the coated paper as described above or a composite of the coated paper and the cardboard or paperboard as described above.
[0155] The features of the application according to the invention are similarly applicable to the packaging according to the invention.
[0156] Packaging can be cold-sealed. Cold-sealed packaging is preferred for packaging foods such as chocolate, chocolate-containing products, bars such as cereal bars, and / or other confectionery products. This is due to the heat sensitivity of chocolate and potentially higher machine speeds. Cold-sealed packaging machines can operate faster because heating the heat-sealing medium requires a relatively long time.
[0157] Packaging can also be heat-sealed. Heat-sealed packaging is preferably suitable for use as secondary packaging or for packaging containers that exceed metering and filling specifications.
[0158] The packaging can also be cold-sealed.
[0159] Packaging can also be molded-filled-sealed packaging, especially cold-sealed or cold-sealed molded-filled-sealed packaging.
[0160] The invention will now be explained in detail based on non-limiting embodiments.
[0161] Example
[0162] The following coating was applied to a 60 g / m² fiber with a content of 40% long fibers and 60% short fibers. 2 Raw paper.
[0163] Pre-coat / primer:
[0164] The pre-coating contains 75.9% pigment (layered silicate), 22.8% latex (styrene-butadiene latex), and 1.3% rheology modifier (0.2% acrylate-based thickener and 1.1% zirconium-based crosslinking agent).
[0165] Barrier layer:
[0166] In Examples 1 to 5 and Comparative Example 1, polyvinyl alcohol was used. In Examples 6 and 7, polyvinyl alcohol was used.
[0167] The barrier layers of Examples 1 to 7 and Comparative Example 1 comprise a pure polymer coating. Example 1' comprises a polymer coating having 99.8% polyvinyl alcohol (Example 1; degree of saponification: 87%; Mw: 50900) and 0.2% rheology modifier (sodium docusate).
[0168] For this purpose, a pre-coating was applied using a blade. The barrier layers of Examples 1 to 7 and Comparative Example 1 were applied using a doctor blade; compared to Example 1, the barrier layer of Example 1' was applied using a curtain coating machine.
[0169] Test the following characteristics:
[0170] Coating weight: The applied weight of the barrier coating, expressed in g / m². This is determined by the weight difference between coated and uncoated paper.
[0171] Viscosity: The viscosity was measured using a Brookfield viscometer at 23°C and 100 rpm, with a dry content of 4%.
[0172] WVTR: Water vapor transmission rate, determined according to ISO 15106-2.
[0173] OTR: Oxygen Transmission Rate, determined according to DIN 15105-2.
[0174] HVTR: Hexane vapor transmission rate. Here, n-hexane is placed in a beaker (solvent-resistant), sealed with the test sample, and the weight reduction over time is monitored. For samples with creases, a 180° crease is created using a roller, which applies a load of 330 g / cm on the created crease. The coating can be located on the inside (inner crease) or the outside (outer crease).
[0175] Palm kernel oil test: similar to DIN 53116. For samples with creases, use a roller to create a 180° crease, applying a load of 330 g / cm on the crease. The crease can be located on the inside (inner crease) or the outside (outer crease).
[0176] Display paper: Evaluate the display paper mentioned in DIN 53116. Here, calculate the grease penetration point for diameters (d) > / < 1 mm.
[0177] Sample paper: Evaluate the back of the sample paper mentioned in DIN 53116. This is not part of the standard, but is done to improve differentiation.
[0178] Sealing joint strength: The samples were sealed for 0.3 seconds at 3.3 bar in the transverse direction of paper running at a temperature range of 100°C to 220°C, and the sealing joint strength was determined according to DIN 55529 (2012). For comparison, the optimal sealing temperature and the sealing force at 150°C (the optimal sealing temperature of Example 1) were recorded.
[0179] DSC melt temperature / starting point:
[0180] DSC curves were measured using a Mettler DSC 20 S in a cold-welded aluminum crucible and perforated cap. The heating rate was 10 K / min, ranging from 30°C to 280°C. The melting temperature was determined by the peak-minimum values of the melting process.
[0181] Surface tension or energy
[0182] OCA 20 (DataPhysics) contact angle measuring instrument with SCA 20 software.
[0183] Measurement principle: OWRK method (Owens, Wendt, Rabel, Kaelble)
[0184] The source of the liquid used in the measurement and the input material constant:
[0185] Water and diiodomethane (according to Buscher) and 1,5-pentanediol (according to Gebhardt)
[0186] The coated paper obtained from the test. The results are shown in the table below.
[0187]
[0188] The partially saponified polyvinyl alcohols used have very low hexane and oxygen permeability. This is likely due to their relatively high hydrophilicity.
[0189] Polyvinyl alcohol with a high degree of saponification is characterized by a higher viscosity in coatings at the same dry content. From a chemical point of view, this makes sense because, due to its higher polarity, each molecule interacts more strongly with the surrounding solvent (water).
[0190] This is quite disadvantageous because a large amount of water must be dried during the coating process with low dry content. This is not only costly in terms of energy, but also difficult to achieve technically, depending on the desired coating weight. Furthermore, the diffusion and drying of water molecules are slowed down. Additionally, this can lead to the accumulation of gaseous water in the coating, resulting in macroscopic coating defects.
[0191] The water vapor transmission rate of the tested polyvinyl alcohol was lower than that of polyvinyl alcohol, which may be due to the ethylene content and the correspondingly lower hydrophilicity.
[0192] Generally, fully saponified PVOH should be more brittle than partially saponified PVOH because they can form more hydrogen bonds. This also applies to Comparative Example 1 (see Palm Kernel Oil Test).
[0193] For Example 2, this has not yet been confirmed. The reason is thought to be the higher molecular weight. For polyvinyl alcohol fibers, it has been shown (e.g., Gotoh et al., Polymer Journal, Vol. 32, no. 12 (2000), pp. 1049-1051: "Molecular Weight Dependence of Tensile Properties in Poly(vinylalcohol) Fibers") that different molecular weights among otherwise identical polyvinyl alcohols have a significant impact on their physical properties. For example, higher molecular weight polyvinyl alcohols have lower elongation at break, but require many times more force to achieve this.
Claims
1. A coated paper comprising a base paper and a barrier layer applied thereon, wherein the barrier layer comprises at least one polymer, characterized in that, The polymer comprises at least partially saponified polyvinyl alcohol and / or at least partially saponified polyvinyl alcohol copolymers, each having an onset temperature less than 210°C as determined by DSC. The onset temperature is defined by DSC according to DIN EN ISO 11357-1:2010-03 as the intersection of the extrapolated baseline and the inflection point tangent at the start of the melting or crystallization peak, wherein other layers containing metals and / or metal oxides are directly applied to the barrier layer.
2. The coated paper according to claim 1, characterized in that, There is a pre-coating containing at least one inorganic pigment and polymer binder between the base paper and the barrier layer.
3. The coated paper according to claim 2, characterized in that, The inorganic pigment is in the form of flakes and includes precipitated calcium carbonate or silicate, and / or the polymer binder comprises a polyacrylate-based polymer binder.
4. The coated paper according to claim 1, characterized in that, The at least one polymer comprises partially saponified polyvinyl alcohol with a saponification degree of 30% to 95%, an average molecular weight greater than 0 and less than 100,000 g / mol, and an onset temperature less than 200°C as determined by DSC.
5. The coated paper according to claim 1, characterized in that, The at least one polymer comprises partially saponified polyvinyl alcohol with a degree of saponification greater than 95% to 100%, an average molecular weight greater than 70,000 g / mol, and an onset temperature less than 200°C as determined by DSC.
6. The coated paper according to claim 1, characterized in that, The at least one polymer comprises a partially saponified polyvinyl alcohol copolymer having a saponification degree of 95% to 100%, an average molecular weight greater than 60,000 g / mol, and an onset temperature less than 210°C as determined by DSC.
7. The coated paper according to claim 1, characterized in that, The at least one polymer comprises a mixture of the following substances: partially saponified polyvinyl alcohol having a saponification degree of 30% to 95%, an average molecular weight greater than 0 and less than 100,000 g / mol, and an onset temperature less than 200°C as determined by DSC; partially saponified polyvinyl alcohol having a saponification degree of greater than 95% to 100%, an average molecular weight greater than 70,000 g / mol, and an onset temperature less than 200°C as determined by DSC; and partially saponified polyvinyl alcohol copolymer having a saponification degree of 95% to 100%, an average molecular weight greater than 60,000 g / mol, and an onset temperature less than 210°C as determined by DSC.
8. The coated paper according to claim 1, characterized in that, At a dry content of 4%, the partially saponified polyvinyl alcohol and / or the partially saponified polyvinyl alcohol copolymer have a Pa0 of less than 30 mPa. The viscosity of s.
9. The coated paper according to claim 1, characterized in that, The areal density of the barrier layer applied is 5 to 20 g / m² relative to the dried final product. 2 .
10. The coated paper according to claim 1, characterized in that, The coated paper does not contain halogen-containing compounds.
11. The coated paper according to claim 1, characterized in that, The areal density of the base paper is 20 to 120 g / m³. 2 .
12. The coated paper according to claim 1, characterized in that, The base paper has a long fiber content of 10 to 80% by weight and a short fiber content of 20 to 90% by weight, wherein the long fibers are fibers with a fiber length of 2.6 to 4.4 mm and the short fibers are fibers with a fiber length of 0.7 to 2.2 mm.
13. The coated paper according to claim 1, characterized in that, The metal is aluminum.
14. A method for producing coated paper according to any one of claims 1-13, characterized in that, An aqueous suspension containing a barrier layer starting material is applied to a base paper, wherein the applied aqueous suspension has a solid content of 5 to 50% by weight, and is applied by a curtain coating method at a coating equipment operating speed of at least 200 m / min.
15. A food packaging material or a component thereof comprising the coated paper of any one of claims 1-13.
16. Packaging comprising coated paper, characterized in that, The coated paper is obtained by the method of claim 14, and the packaging is a cold-sealed packaging, a heat-sealed packaging, or a form-fill-seal packaging.
17. The coated paper according to claim 2, characterized in that, The inorganic pigment is in flake form and includes talc, precipitated calcium carbonate or kaolin, and / or the polymer binder comprises a polyacrylate-based polymer binder.
18. The coated paper according to claim 1, characterized in that, The at least one polymer comprises partially saponified polyvinyl alcohol with a degree of saponification of 95% to 100%, an average molecular weight greater than 60,000 g / mol, and an onset temperature less than 210°C as determined by DSC.
19. The coated paper according to claim 1, characterized in that, At a dry content of 4%, the partially saponified polyvinyl alcohol and / or the partially saponified polyvinyl alcohol copolymer have a Pa0.01 of less than 15 mPa. The viscosity of s.
20. The coated paper according to claim 1, characterized in that, The areal density of the barrier layer applied is 8 to 12 g / m² relative to the dried final product. 2 .
Citation Information
Patent Citations
methods for manufacturing an information recording material and coating solutions for use in this material
DE10196052T1
VARIANT RNAi
US20200109401A1
PVOH-based coating solutions
US6444750B1
Barrier coatings post-treated with multi-valent metal cations
WO2010129032A1
Laminated packaging material, packaging containers manufactured therefrom and a method for manufacturing the laminate material
CN108290384A